Pengaruh Earning per Share, Return on Asset, Return on Equity, dan Net Profit Margin terhadap Harga Saham - Henri Wibowo; Yeni Kuntari (STIE Widya Manggala, 2014)
This research aimed to find out the influence of Earning per Share, Return On Asset, Return On Equity, and Net Profit Margin on the stock price of Wholesale and Retail Companies in 2009-2011 in Indonesia Stock Exchange either simultaneously or partially. The sampling technique used was Purposive Sampling method. There were 10 companies that could be analysed. The model regression used was by multiple linier regression. The result showed that simultaneously at level of significance 5% EPS, ROA, ROE, and NPM had a significant influence on the stock price of Wholesale and Retail. Partially at the level of significance 5% the result showed that EPS, ROE, and NPM had negative and significant influence on the stock price, meanwhile variable ROA had a positive and significant on the stock price. And in this research EPS, ROA, ROE, and NPM could explain the stock price as high as 28,7% and the remaining value 71,3% was influenced by other variables outside the model such as Book Value, The discount rate, risk-free interest rate, the market interest rate and market risk